Tigecycline Interferes with Fibrinogen Polymerization Independent of Peripheral Interactions with the Coagulation System - Anna Brandtner; Mirjam Bachler; Dietmar Fries; Martin Hermann; Jacqueline Ruehlicke; Vilmos Fux; Andrea Griesmacher; Christian Niederwanger; Tobias Hell; Benedikt Treml (MDPI AG, 2020)
Tigecycline offers broad anti-bacterial coverage for critically ill patients with complicated infections. A described but less researched side effect is coagulopathy. The aim of this study was to test whether tigecycline interferes with fibrinogen polymerization by peripheral interactions. To study the effect of unmetabolized tigecycline, plasma of healthy volunteers were spiked with increasing concentrations of tigecycline. In a second experimental leg, immortalized human liver cells (HepG2) were treated with the same concentrations to test an inhibitory effect of hepatic tigecycline metabolites. Using standard coagulation tests, only the activated thromboplastin time in humane plasma was prolonged with increasing concentrations of tigecycline. Visualization of the fibrin network using confocal live microscopy demonstrated a qualitative difference in tigecycline treated experiments. Thrombelastometry and standard coagulation tests did not indicate an impairment of coagulation. Although the discrepancy between functional and immunologic fibrinogen levels increased in cell culture assays with tigecycline concentration, fibrinogen levels in spiked plasma samples did not show significant differences determined by functional versus immunologic methods. In our in vitro study, we excluded a direct effect of tigecycline in increasing concentrations on blood coagulation in healthy adults. Furthermore, we demonstrated a rapid loss of mitochondrial activity in hepatic cells with supra-therapeutic tigecycline dosages.